2020
DOI: 10.3390/genes11121509
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Inflammation on Cytochrome P450 Regulation and Drug Metabolism: Lessons from Experimental Models and a Potential Role for Pharmacogenetics

Abstract: Personalized medicine strives to optimize drug treatment for the individual patient by taking into account both genetic and non-genetic factors for drug response. Inflammation is one of the non-genetic factors that has been shown to greatly affect the metabolism of drugs—primarily through inhibition of cytochrome P450 (CYP450) drug-metabolizing enzymes—and hence contribute to the mismatch between the genotype predicted drug response and the actual phenotype, a phenomenon called phenoconversion. This review foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 105 publications
(149 reference statements)
3
102
2
Order By: Relevance
“…72 CYB2B6 was shown to be expressed in prostate epithelial cells and suppressed in prostate cancer cells, its downregulation correlates with poor prognosis and its overexpression inhibits proliferation in LNCaP prostate cancer cells. 73 Inflammatory cytokines, especially IL-6, generally downregulate the expression of cytochrome P450 enzymes 74 , but how their suppression contributes to inflammation and fibrosis in the prostate is unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…72 CYB2B6 was shown to be expressed in prostate epithelial cells and suppressed in prostate cancer cells, its downregulation correlates with poor prognosis and its overexpression inhibits proliferation in LNCaP prostate cancer cells. 73 Inflammatory cytokines, especially IL-6, generally downregulate the expression of cytochrome P450 enzymes 74 , but how their suppression contributes to inflammation and fibrosis in the prostate is unclear and needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated a correlation between P450 isoform expression levels and cytokines levels [ 56 , 57 , 58 ]. An in vitro study examined the effect of five pro-inflammatory cytokines IL-1β, IL-4, IL-6, TNF-α and interferon gamma (IFN-γ) on the expression of CYP1A2, CYP2C, CYP2E1, CYP3A in primary human hepatocyte cultures [ 59 ].…”
Section: P450 Regulation and Inflammationmentioning
confidence: 96%
“…Drug metabolizing enzymes such as P450s are regulated at transcriptional and post-transcriptional levels [ 55 ]. Regulation of P450 mRNA levels by factors such as transcription factors such as the nuclear receptor pregnane X receptor (PXR) and its dimerization with retinoid X receptor (RXR), is responsible for the observed downregulation of P450 enzymes under inflammatory conditions [ 56 ]. Furthermore, it has been suggested that transcription factor nuclear factor-kappa B (NF-κB) could control the expression of several P450 enzymes through its interaction with the promotor region of their genes [ 56 ] ( Figure 1 ).…”
Section: P450 Regulation and Inflammationmentioning
confidence: 99%
“…Inflammation-induced dysregulation patterns of UGTs are probably pathology-dependent, tissue-specific and isoform-heterogeneous. The direction and extent of change depend on the type of inflammation, cytokine spectrum and time course (36,37). In rat colitis model, the expression and activity of hepatic UGTs were significantly down-regulated except for the up-regulation of UGT1A7, but those in small intestine were unaffected (36).…”
Section: Mpo Play An Integral Role In Aanmentioning
confidence: 99%